Penerapan Teknik Lobi Dan Negosiasi Yang Efektif Dalam Melakukan Bisnis UMKM Di Kota Medan - Suhairi Suhairi; Rabiatun Adawiyah; Rofiqoh Hannum Rao; Cindy Kumala Dewi; Leni Lastrian Nahulae (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Lobbying and negotiation techniques are a part of communication origins which play an important role in business activities. Effective lobbying and negotiation affect the smooth running of a business because it can help shape relationships and collaboration between business partners in a company and is also able to establish good communication to reach mutual agreements. The purpose of this study is to analyze techniques, tactics and introduce the Medan mayor's lobbying techniques for the advancement of MSMEs in the city of Medan, there are various ways that need to be developed in order to successfully lobby and negotiate every business activity. This research uses the library research method, which is a method that uses secondary data sources by looking for certificates through journals, books, literature, notes, and various other documents related to the problem to be solved. The results of the study stated that the success of lobbying and negotiating in a business depends on senior management and skills when lobbying and negotiating exclusive parties. Lobbying and negotiation techniques in business also require an effective communication process so as not to create understanding between the parties conducting lobbying and negotiations and need to know how to convey messages from the parties being lobbied or negotiated and position themselves properly during the negotiation process.